Simultaneous determination of evodiamine and its four metabolites in rat plasma by LC–MS/MS and its application to a pharmacokinetic study. (2nd April 2018) - Wang, Cuiyun; Yue, Fang; Ai, Guangfeng; Yang, Jie
Abstract: A simple and sensitive liquid chromatography tandem mass spectrometry method was validated for simultaneous quantification of evodiamine and its metabolites 10‐hydroxyevodiamine (M1), 18‐hydroxyevodiamine (M2), 10‐hydroxyevodiamine‐glucuronide (M3) and 18‐hydroxy‐ evodiamine‐glucuronide (M4) in rat plasma for the first time. The analytes were extracted with acetonitrile and separated on a C18 column within 3 min. The detection was achieved in positive selected reaction monitoring mode with precursor‐to‐product transitions at m/z 304.1 → 161.1 for evodiamine, m/z 320.1 → 134.1 for M1, m/z 320.1 → 150.1 for M2, m/z 496.2 → 134.1 for M3, m/z 496.2 → 171.1 for M4 and m/z 349.2 → 305.1 for camptothecin (internal standard). The linearity was evident over the tested concentration ranges with correlation coefficients >0.9991. The lower limits of quantification for evodiamine, M1, M2, M3 and M4 were 0.1, 0.1, 0.1, 0.25 and 0.25 ng mL −1, respectively. Extraction recoveries and matrix effects of the analytes were within the ranges of 84.51–97.21 and 90.13–103.30%, respectively. The accuracy (relative error) ranged from −8.14 to 7.23% while the intra‐ and inter‐day precisions (relative standard deviation) were < 9.31%. The validated assay was successfully applied for the pharmacokinetic study of evodiamine, M1, M2, M3 and M4 in rat. The current study will be helpful in understanding the in vivo disposition of evodiamine.